2017
DOI: 10.14740/jem441w
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hormonal Contraception on Vitamin D Supplementation on Serum 25(OH)D3 Status in Premenopausal Women: A Prospective Double-Blind Placebo Random Controlled Trial

Abstract: Background: A number of cross-sectional studies have highlighted a potential benefit of estrogen-containing contraception on serum 25-hydroxyvitamin D (25(OH)D) levels. The purpose of the present prospective study was to determine whether oral vitamin D 3 supplementation significantly increases serum 25(OH)D more for women taking the estrogen-containing oral contraception than those not taking this medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Wyon et al reported a small-scale, prospective, double-blind placebo RCT in which estrogen-containing oral contraceptives increased serum 25(OH)D in premenopausal women, with a magnified effect in women taking vitamin D supplements. 21 Harmon et al reported that estrogen-containing contraceptives were associated with a 20% increase in 25(OH)D concentration in a large study of African American women in one area of northern latitude. 22 Lastly, Ciebiera et al suggested that oral contraceptive use is associated with higher 25(OH)D concentrations in a healthy patient population of premenopausal Caucasian women of northern latitude who were not pregnant or breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Wyon et al reported a small-scale, prospective, double-blind placebo RCT in which estrogen-containing oral contraceptives increased serum 25(OH)D in premenopausal women, with a magnified effect in women taking vitamin D supplements. 21 Harmon et al reported that estrogen-containing contraceptives were associated with a 20% increase in 25(OH)D concentration in a large study of African American women in one area of northern latitude. 22 Lastly, Ciebiera et al suggested that oral contraceptive use is associated with higher 25(OH)D concentrations in a healthy patient population of premenopausal Caucasian women of northern latitude who were not pregnant or breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…To account for potential drop out 10 participants were recruited per group. Exclusion criteria included any participant that was taking vitamin supplementation, were non-Caucasian, had a skin condition that would prevent them from applying oil to their skin or were taking, had taken a sunny holiday in the last 6-months, planned to take a sunny holiday during the study period, or had been taking in the past 6-months, oestrogen-based contraception 25 . Seventy Caucasian volunteers were recruited from a female university population that included students and academics (latitude 52.58 o N) during the month of March.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies show a correlation between OC use and reduced levels of vitamin B12 and vitamin B6 [ 139 ]. A change in vitamin D levels associated with oral estrogens has also been found [ 140 ]. Thus, some data suggest that dietary management may not be effective in reducing PMS symptoms [ 141 ].…”
Section: Managing Pmsmentioning
confidence: 99%